The Relationship between Teacher Collaboration and Work Environment on Work Comfort - Putri Zakia Agustin; Rubini; Siti Marpuah (JIEMAN: Journal of Islamic Educational Management, 2025)
This study aims to examine the relationships among teacher collaboration, the work environment, and job comfort. A quantitative research approach was employed, using a saturated sampling technique in which the entire population served as the research sample, given its relatively small size. The participants of this study were 30 teachers at SMP Negeri 1 Sagalaherang, Subang City. Data were collected using a Likert-scale questionnaire designed to measure the levels of teacher collaboration, work environment conditions, and job comfort. The collected data were analysed using multiple linear regression in SPSS version 27. The analysis indicates that teacher collaboration has a significant positive effect on job comfort, suggesting that effective cooperation, communication, and teamwork among teachers contribute to a more comfortable work environment. In addition, the work environment was found to be significantly related to job comfort, suggesting that physical, social, and psychological working conditions play an important role in supporting teachers’ well being. Simultaneously, teacher collaboration and the work environment were proven to have a significant combined effect on job comfort. These findings highlight the importance of fostering collaborative practices and creating a supportive work environment to enhance teachers’ job comfort and overall performance in educational institutions.